Prenatal diagnosis of tetralogy of Fallot with pulmonary atresia using Fetal Intelligent Navigation Echocardiography (FINE) - Yeo, Lami (J Matern Fetal Neonatal Med, 2018)
Tetralogy of Fallot is comprised of a subaortic ventricular sepal defect, overriding aorta, and infundibular pulmonary stenosis. A severe form of this congenital heart defect is tetralogy of Fallot with pulmonary atresia (TOF/PA), characterized by absence of flow from the right ventricle to the pulmonary arteries. This is one of the most challenging and complex cardiac defects due to its many different anatomic variants. A novel method developed recently, known as Fetal Intelligent Navigation Echocardiography (FINE), allows automatic generation of nine standard fetal echocardiography views in normal hearts by applying “intelligent navigation” technology to spatiotemporal image correlation volume datasets. We report herein for the first time, two cases of TOF/PA with variable pulmonary arterial anatomy in which the FINE method successfully demonstrated the features of this condition prenatally.